Exploring how Japanese pharmacists provide reasonable accommodations for persons with intellectual disabilities - Masaki Shoji; Rintaro Imafuku; Mei Mizomoto; Mitsuko Onda (BMC Health Services Research)
Abstract Background There has been limited progress in research on reasonable accommodations for persons with mild/moderate intellectual disabilities (ID) who are able to live independently but have struggles. This study aims to qualitatively investigate how pharmacists provide reasonable accommodations when communicating with people with ID. Methods Between October 2023 and March 2024, semi-structured interviews were conducted with 11 hospital or community pharmacists. They were mainly asked about how they have dealt with people with ID. Interviews were conducted either in person or online, each lasting 30–60 min. Data were analyzed using a thematic analysis approach. Results This study identified three main themes regarding the pharmacists’ reasonable accommodation practices: “comprehension aids,” “reminders,” and “structural accommodations.” Specifically, to help the individuals better understand, pharmacists tried to use simple expressions and visual information, including pictures and symbols, and to adjust their speaking speed and volume. As reminder strategies, they provided supplementary handwritten information, highlighted the main points, and use of post-its. Furthermore, they illustrated the medication sequence as a structural accommodation strategy. Conclusions The study suggests that pharmacists have employed several strategies to offer reasonable accommodations, aiming to build and maintain better relationships with people with ID and to promote these individuals’ understanding of medications, adherence, and treatment safety.